This believing world : a simple account of the great religions of mankind - Browne, Lewis, 1897-1949 (The Macmillan company, 1929)
Examines primitive religion; Celtic, Greek, Babylonian. Egyptian, and Roman religions; Brahmanism; Janinism; Buddhism; Hinduism; Confucianism; Taoism; Judaism; Zoroastrianism; Christianity; and Mohammedanism.